Whose Calendar? - Stonebraker, Michael (Communications of the ACM, 2015)
The author presents a letter to the editor in which he corrects a statement he made in the article by Leah Hoffmann titled “The Path to Clean Data” in the June 2015 issue; the term he meant to use was Gregorian calendar.